A novel colorimetric sensor array based on boron-dipyrromethene dyes for monitoring the storage time of rice. (1st December 2018) - Lin, Hao; Man, Zhong-xiu; Kang, Wen-cui; Guan, Bin-bin; Chen, Quan-sheng; Xue, Zhao-li
Highlights: The compound of 18-crown-6 was found obviously changed during rice aging process. A kind of boron-dipyrromethene was found sensitive to the compound of 18-crown-6. Optimal colorimetric sensor array monitored the storage time of rice accurately. Abstract: A novel colorimetric sensor array based on boron-dipyrromethene (BODIPY) dyes was developed to monitor the volatile organic compounds (VOCs) of rice at different storage times. The VOCs of rice at different storage times were analyzed through GC–MS combined with multivariate analysis, and the compound 18-crown-6 was found significantly changed during rice aging process. Aimed at 18-crown-6 with particular macrocyclic structure, a series of BODIPYs were targeted synthesized for the selection of sensitive chemically responsive dyes. Four dyes were chosen to construct colorimetric sensor array based on sensitivity to VOCs of aged rice samples. Data acquired from the interactions of dyes and rice VOCs were subjected to the principal components analysis (PCA) and linear discriminant analysis (LDA). The optimal performance obtained by the LDA model was 98.75% in prediction set. Application of BODIPYs in this work has improved the sensitivity and expanded the choices of colorimetric dyes for the specific detection.